Collared Silicone Punctal Plugs Compared to Intracanalicular Plugs for the Treatment of Dry Eye. (May 2013) - Rabensteiner, Dieter Franz; Boldin, Ingrid; Klein, Angelika; Horwath-Winter, Jutta
Abstract Aim: To compare collared silicone punctal plugs to intracanalicular SmartPlugs for the treatment of moderate to severe dry eye. Materials and methods: In this prospective, randomized, single blind, clinical study, 30 patients (60 eyes) who had been diagnosed with moderate to severe dry eye syndrome were enrolled. Study group I (n = 30 eyes) received collared silicone punctal plugs and group II (n = 30 eyes) received intracanalicular SmartPlugs. Data for the Schirmer I test, tear break-up time, vital staining, subjective symptoms and frequency of artificial tear application were recorded at baseline and 3 months after punctal occlusion. Results: There was no statistical significant difference for these values between group I and II. Conclusions: Although published data show free flow with irrigation and probing after SmartPlug insertion, the clinical effect in the treatment of dry eye appears to be the equally well to collared silicone punctal plugs. It seems likely that difference of design and localization between the treatment groups were of minor importance concerning impeding of natural and supplemental moisture.